Castrating dogs: why, when, how?. (2nd October 2022) - Hoad, Julian
Abstract : Castration is one of the most commonly performed surgical procedures in the UK, and yet there is little in the way of consistency among practices in the advice given to owners wishing to have their dog neutered. Opinions are often conflicting in terms of pros and cons of castration and the ideal timing. This article considers some of the available evidence and tries to resolve some of the ambiguity where possible.